World-wide survey on the treatment of peripheral vestibular disorders - Strupp, Michael; Kern, Nils Lucca; Laurell, Göran; Lehner, Louisa; Grill, Eva; Strobl, Ralf (Frontiers in Neurology, 2025)
ObjectiveThe aim of this world-wide survey was to evaluate the currently applied treatment options for the six most frequent peripheral vestibular disorders: benign paroxysmal positional vertigo (BPPV), acute unilateral vestibulopathy (AUVP)/vestibular neuritis, Menière’s disease (MD), bilateral vestibulopathy (BVP), vestibular paroxysmia (VP) and superior canal dehiscence syndrome (SCDS).BackgroundFor the therapy of vestibular disorders, there are four treatment options: vestibular physical therapy (canalith repositioning maneuvers or balance training), pharmacotherapy, surgery, and psychotherapy. Since there are very few state-of-the-art RCTs, the treatment of vestibular disorders is so far not standardized and various methods are applied with heterogeneous efficacy.Design/methodsA web-based standardized survey questionnaire on the treatment of the six most frequent peripheral vestibular disorders was used to collect data.Results234 replies from five continents, 47 countries, 162 cities and 188 centers were received: (% from all 234 replies; multiple answers possible): BPPV: posterior canal BPPV: 71% Epley, 40% Semont, and 12% others. Horizontal canal BPPV canalolithiasis: 58% Lempert (roll-over) maneuver, 33% Gufoni, 7% prolonged rest, and 9% others. Horizontal canal BPPV cupulolithiasis: 35% Gufoni, 27% Lempert (roll-over) maneuver, 9% Zuma, and 7% head shaking: AUVP: 79% pharmacotherapy, namely 47% glucocorticoids, 39% antiemetics, and 24% betahistine; 67% vestibular physical therapy. MD: 85% pharmacotherapy, namely 65% betahistine, 21% diuretics, 20% steroids, 16% antiemetics, 14% gentamicin; 37% surgery. VP: 65% pharmacotherapy, namely 57% anticonvulsants; 7% surgery. BVP: 77% vestibular physical therapy. SCDS: 50% surgery, namely 38.8% canal plugging, 23.3% capping and 15.5% resurfacing.ConclusionIn this world-wide survey with 234 replies from 188 centers, widely heterogeneous applied treatment options were reported for the six most frequent peripheral vestibular disorders. This study shows in particular that certain drugs are often used despite low or very low evidence. Namely in AUVP, MD and VP well-designed controlled trials with clinically meaningful endpoints are needed.